A Novel SNPs of the SREBF1 and SCARB1 Genes and the Association with Fatty Acid Profile in Bali Cattle - Dairoh; Ulum, M. F.; Jakaria; Ishak, A. B. L.; Sumantri, C. (Faculty of Animal Science, Bogor Agricultural University, 2023)
This study aimed to investigate the genetic impact of single nucleotide polymorphisms (SNPs) of the sterol regulating element binding factor 1 (SREBF1) and scavenger receptor class B member 1 (SCARB1) genes on carcass and meat characteristics, as well as fatty acid composition, in the Bali cattle. The blood and beef samples used for DNA sequencing, physical assessment, and fatty acid analysis were collected from 95 male Bali cattle. The ultrasound images were analyzed using the Image-J NIH software. A total of 4 SNPs were identified in the SREBF1 gene and 5 SNPs in the SCARB1 gene. The results showed that the 4 SNPs in the SREBF1 gene, namely g.12629T>C, g.12731T>C, g.12881A>G, and g.12986C>T, were associated with heptadecanoic acid (C17:0) and cis-11-eicosanoic acid (C20:1). The SNPs g.12731T>C of the SREBF1 gene was associated with fat content, palmitoleic acid (C16:1), stearic acid (C18:0), cis-11-eicosanoic acid (C20:1), and total fatty acids. Furthermore, 4 SNPs in the SCARB1 gene, including g.72219C>T, g.72380C>A, g.72517G>A, and g.72607C>T correlated with longissimus dorsi thickness (LDT). All SNPs in the SCARB1 gene showed significant associations with cis-10 heptadecanoic acid (C17:1) and cis 8,11,14-eicosatrienoic acid (C20:3n6). The SNP g.72400A>G of the SCARB1 gene was related to caprylic acid (C8:0), lauric acid (C12:0), arachidonic acid (C20:4n6), monounsaturated fatty acids (MUFA), and unsaturated fatty acids (UFA). These results suggested that the identified polymorphisms in the SREBF1 and SCARB1 genes could serve as valuable references for investigating similar genes in other cattle breeds, particularly concerning fatty acids.